A novel mutation of COL7A1 in a Chinese DEB‐Pt family and review of the literature. (10th November 2019) - Jin, Ling; Li, Zhi; Xin, Cong; Tang, Lili; Zhang, Xuejun; Zhang, Bo; Yang, Sen
Abstract: Background: Pretibial dystrophic epidermolysis bullosa (DEB‐Pt) is an extremely rare subtype of dystrophic epidermolysis bullosa (DEB) characterized by blistering and scar formation. The pathogenesis of the disease is mainly due to the mutation of COL7A1 gene encoding type VII collagen fibers, resulting in the destruction of the anchoring structure of the epidermis and dermis. Aims: The purpose of this study was to discover the major mutations in DEB‐Pt by studying this family and reviewing the literature on DEB‐Pt. Patients/Methods: We examined the patients by clinical manifestations and histopathology, extracted DNA from blood samples from 7 individuals in the family via FlexiGene DNA Kit, and then sequenced the samples using whole‐exon sequencing (WES). Result: Characteristic clinical manifestations such as blisters and scars were found in the patients. Genetic analysis revealed a missense mutation in exon 87(c.6860G>A) of COL7A1 gene, which has never been reported before. Conclusion: The discovery of the new mutation extends the COL7A1 mutation database. We also reviewed all the mutation in DEB‐Pt from relevant literature at home and abroad. This will facilitate the molecular diagnosis, treatment, and prognosis of DEB‐Pt.